2021
DOI: 10.3390/ijerph182312445
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Literature Review of Bias in Collecting Patient Reported Outcomes Measures (PROMs)

Abstract: There is a growing interest in the collection and use of patient reported outcomes because they not only provide clinicians with crucial information, but can also be used for economic evaluation and enable public health decisions. During the collection phase of PROMs, there are several factors that can potentially bias the analysis of PROM data. It is crucial that the collected data are reliable and comparable. The aim of this paper was to analyze the type of bias that have already been taken into consideratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 30 publications
(29 reference statements)
0
29
0
Order By: Relevance
“…Although there are several advantages to electronic versions of PROs (e.g., real-time data recording, immediate scoring, and reduction of human error), the implementation of traditional paper-based methods avoids the exclusion of certain patients who are less comfortable using electronic devices. Several studies have reported no significant differences between the two modes [ 39 ]. In addition, high compliance rates for completion of the EORTC QLQ-C30 and the FACIT-F were observed with very few dropouts across both treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are several advantages to electronic versions of PROs (e.g., real-time data recording, immediate scoring, and reduction of human error), the implementation of traditional paper-based methods avoids the exclusion of certain patients who are less comfortable using electronic devices. Several studies have reported no significant differences between the two modes [ 39 ]. In addition, high compliance rates for completion of the EORTC QLQ-C30 and the FACIT-F were observed with very few dropouts across both treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…As a retrospective analysis of prospectively collected data, it is impacted by recall bias. 35 Our mean follow-up of 13 months reports short-term outcomes and future studies looking at mid- and long-term outcomes could potentially be useful. Further, the relatively small number of patients in the study could mean that we were underpowered to find significant differences across all domains, and a power analysis was not performed.…”
Section: Discussionmentioning
confidence: 93%
“…These patients, as they never participated, should potentially be considered as “screening failure” instead of being categorized as “lost to follow-up”. In the future, deleting data of those patients who have not reported their preoperative assessment by a predetermined time (at which potential recollection bias may impact data quality) may be considered [ 26 ]. Nonetheless, effort should be made in order to increase the follow-up rate and decrease the rate of “screening failures”.…”
Section: Discussionmentioning
confidence: 99%